Community coalition readiness for implementing something new: Using a Delphi methodology. Issue 4 (28th January 2019) - Domlyn, Ariel M.; Wandersman, Abraham
Abstract: Organizational readiness for an innovation (a program, policy, or practice new to a setting) is important for successful implementation. The R = MC 2 heuristic focuses on capacity and motivation as a framework for readiness; it comprises 3 components and 18 subcomponents. A Delphi study with community coalition leaders was undertaken to assess when each subcomponent is most significant in the life cycle of implementing an innovation in a coalition. Results include that motivation is viewed as most important in the early stages of implementation and leadership, climate, program champions, and interorganizational relationships are relevant throughout the lifespan of implementation. Results have implications for the future of assessing and building coalition readiness.